Dissemination of digital map technology for administrative map in Padukuhan Soka, Kandirejo Village - Iswanto Suwarno; Muhammad Ahmad Baballe; Robbi Rahim; Nia Maharani Raharja; Mohammad Aljanabi (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Padukuhan Soka is one of the hamlets that are in the administrative area of Candirejo Village. So that information is needed in the form of administrative maps and public facilities that can be used as a support for the Soka Padukuhan in managing their households. The purpose of this community service is to map the Soka Padukuhan as a basis for regional development in the Soka Padukuhan area, Candirejo Village, Semanu District, Gunungkidul Regency. The methods used include surveys, preparation stages, map making processes, temporary print outs, permanent print outs, and map handover. Community service activities at Padukuhan Soka produce village maps containing geospatial information that can be found in the area. This information is in the form of administrative area boundaries shown on the village map. Therefore, the presentation of the map needs to be updated over time to adjust to the latest conditions in Padukuhan Soka. In development planning, the map is used as material in managing the Soka Padukuhan area so that it makes it easier to find out the administrative areas in the Soka Padukuhan.